The Recall Function of Mass Media: Big Issues Coverages (Communication & Society, 2000)
The article contains a reflection about how, in certain circumstances and about certain issues, the media develop a special procedure, the “dynamics of recall,” which prevent some social topics of being forgotten, despite having gone beyond their cycle of initial interest without being solved out. Based on an empirical study, this paper defines the “recall function” of the media, not registered in the bibliography, and tries to complete some of the theoretical statements made from the functional structural perspective at the half of the century.